Mechanistic Insights into the Cycling Behavior of Sulfur Dry-Film Cathodes - Fiedler, Magdalena; Cangaz, Sahin; Hippauf, Felix; Doerfler, Susanne; Abendroth, Thomas; Althues, Holger; Kaskel, Stefan (Advanced Sustainable Systems, 2023)
All-solid-state lithium–sulfur batteries (ASSB-LiS batteries) are considered among advanced candidates for next-generation energy storage systems, as they break with restrictions and limitations that liquid electrolytes impose on lithium-ion batteries and lithium-sulfur batteries (LiS-batteries), meaning enhanced safety and higher energy densities. However, investigations under realistic conditions on pouch cell level are challenging, as it is necessary to implement a scalable preparation method for sheet-type cathodes with high sulfur utilization and loading. In this study, a solvent-free process to prepare free-standing cathode sheets with low binder content down to 0.1 wt% PTFE is demonstrated. The contribution of binder and electrolyte on the conversion reaction of sulfur is discussed. Sheet-type cathodes reach nearly theoretical sulfur utilization of 1672 mAh gS−1 and outstanding reversible capacity retention with 72% of initial discharge capacity after 400 cycles by adapting cut-off voltages to the stability window of the electrolyte. Furthermore, an all-solid-state pouch cell is demonstrated using the dry-film cathode, which is successfully tested for 50 cycles at different C-rates. Thickness monitoring of the cell stack gives fundamental insights into the volume change and breathing behavior of both cathode and anode.
CRIS-Team Scopus Importer:2023-03-20
Keywords: all-solid-state batteries; electrode sheets; lithium–sulfur batteries; low binder amount; solid electrolytes; solvent-free processing; thiophosphate electrolytes